2017
DOI: 10.2337/ds16-0074
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Eating Pattern

Abstract: IN BRIEF The Mediterranean-style eating pattern (MEP) has long been touted as a healthful way of eating. However, the health benefits of the eating pattern and key elements contributing to those benefits are still being researched. In people with type 2 diabetes, the majority of studies report that the MEP improves glycemic control and cardiovascular risk factors. In people at risk for diabetes, the majority of studies report a protective effect of the MEP against the development of type 2 diabetes. Although m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 22 publications
2
31
0
1
Order By: Relevance
“…As stated in the American Diabetes Association (ADA) guidelines [32], there is not a one-size-fits-all nutritional approach for individuals affected by T2D, and meal planning, delivered by registered dieticians, should be individualized, taking into account current eating patterns, preferences, and specific glycometabolic goals. With this in mind, the MedDiet [33,34], and other plant-based [35,36] nutritional approaches, all associated with positive outcomes in clinical research conditions, can be endorsed as suitable treatment measures to achieve glycemic control, so that the need for pharmacological medications would be minimized. In particular, important health benefits have been demonstrated for the Mediterranean eating pattern, which can considerably improve fasting glucose, glycated hemoglobin (HbA1c) and insulin levels in obese diabetic patients, when compared to low-fat diets [17].…”
mentioning
confidence: 99%
“…As stated in the American Diabetes Association (ADA) guidelines [32], there is not a one-size-fits-all nutritional approach for individuals affected by T2D, and meal planning, delivered by registered dieticians, should be individualized, taking into account current eating patterns, preferences, and specific glycometabolic goals. With this in mind, the MedDiet [33,34], and other plant-based [35,36] nutritional approaches, all associated with positive outcomes in clinical research conditions, can be endorsed as suitable treatment measures to achieve glycemic control, so that the need for pharmacological medications would be minimized. In particular, important health benefits have been demonstrated for the Mediterranean eating pattern, which can considerably improve fasting glucose, glycated hemoglobin (HbA1c) and insulin levels in obese diabetic patients, when compared to low-fat diets [17].…”
mentioning
confidence: 99%
“…Two systematic reviews found limited evidence that the Mediterranean diet is effective for glycaemic control, but more robust support for CVD risk reduction. Also cited was a commentary favouring the Mediterranean diet that was based on a non‐systematic selection of articles …”
Section: Resultsmentioning
confidence: 99%
“…The ADA documents cite six studies, [25][26][27][28][29][30][31] including three RCTs of longer duration, [25][26][27][28] to support claims that a Mediterranean diet can improve glycaemic control and CVD risk factors and is therefore a healthy eating pattern for people with T2D (Table S7). Two RCTs found that the Mediterranean diet was superior to comparison diets 25,28 : one found that a low-carbohydrate Mediterranean diet resulted in a significantly greater HbA1c reduction compared to the control diet, 28 and the other found at 4-year follow-up that the Mediterranean diet resulted in significant HbA1c reduction, sustained improvements in triglyceride and HDL cholesterol levels, and less medication initiation in people with newly diagnosed T2D.…”
Section: Cited Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Cited evidence. The ADA documents cite six studies, [25][26][27][28][29][30][31] including three RCTs of longer duration, [25][26][27][28] to support claims that a Mediterranean diet can improve glycemic control and CVD risk factors and is therefore a healthy eating pattern for people with T2D ( Table 1). Two RCTs found that the Mediterranean diet was superior to comparison diets: 25,28 one found that a low-carbohydrate Mediterranean diet resulted in a significantly greater HbA1c reduction compared to the control diet, 28 and the other found at four-year follow-up that the Mediterranean diet resulted in significant HbA1c reduction, sustained improvements in triglycerides and HDL-C, and less medication initiation in persons with newly diagnosed T2D.…”
Section: Mediterranean Dietmentioning
confidence: 99%